Quarantine during COVID-19 outbreak: Adherence to the Mediterranean diet among the Cypriot population - Kyprianidou, Maria; Christophi, Costas A.; Giannakou, Konstantinos (My University, 2021)
Objective The aim of this study was to analyze adherence to the Mediterranean diet among the adult general population of Cyprus during the COVID-19 confinement. Methods This was an Internet-based, cross-sectional study that collected information about socioeconomic and demographic characteristics, adherence to the Mediterranean diet and other dietary details, physical activity levels, and smoking habits using a self-administered questionnaire. The survey was conducted between April 6 and June 20, 2020, 1 to 2.5 mo after the initiation of the social confinement measures. Results There were 1485 Cypriot adults who participated in the study. The median Mediterranean diet score was 21 (q1 = 19, q3 = 24) with men, married individuals, residents of rural regions, and physically active participants being more adherent to the Mediterranean diet compared with women; unmarried, divorced, or widowed; residents of urban regions; and physically inactive participants, respectively (P < 0.05). Multinomial logistic regression showed that being ≥45 y of age and physically active was positively associated with the Mediterranean diet score, whereas being unmarried, divorced, or widowed and a current smoker was negatively associated with the Mediterranean diet score (P < 0.05). Conclusions Adherence to the Mediterranean diet during the confinement imposed due to the COVID-19 pandemic among the Cypriot adult population was associated with male sex, age >45 y, being married, being physically active, and being resident of rural regions. The importance of better understanding of nutritional behavior during COVID-19 lockdowns is emphasized so public health authorities can plan future lockdown policies on nutritional recommendations, should a new pandemic occur.
Keywords: COVID-19; Cyprus; Mediterranean diet; Coronavirus; Nutrition; Quarantine